Imatinib prevents beta cell death in vitro but does not improve islet transplantation outcome. (2nd April 2016) - King, Aileen J. F.; Griffiths, Lisa A.; Persaud, Shanta J.; Jones, Peter M.; Howell, Simon L.; Welsh, Nils
Abstract: Introduction Improving islet transplantation outcome could not only bring benefits to individual patients but also widen the patient pool to which this life-changing treatment is available. Imatinib has previously been shown to protect beta cells from apoptosis in a variety of in vitro and in vivo models. The aim of this study was to investigate whether imatinib could be used to improve islet transplantation outcome. Methods Islets were isolated from C57Bl/6 mice and pre-cultured with imatinib prior to exposure to streptozotocin and cytokines in vitro . Cell viability and glucose-induced insulin secretion were measured. For transplantation experiments, islets were pre-cultured with imatinib for either 72 h or 24 h prior to transplantation into streptozotocin-diabetic C57Bl/6 mice. In one experimental series mice were also administered imatinib after islet transplantation. Results Imatinib partially protected islets from beta cell death in vitro . However, pre-culturing islets in imatinib or administering the drug to the mice in the days following islet transplantation did not improve blood glucose concentrations more than control-cultured islets. Conclusion Although imatinib protected against beta cell death from cytokines and streptozotocin in vitro, it did not significantly improve syngeneic islet transplantation outcome.